Design and Application of Teaching Resources Sharing Platform for Physical Education Major Based on Internet. Issue 2 (August 2021) - Ma, Hongjun
Abstract: In recent years, the problem of excessive obesity and poor physique of teenagers has become increasingly prominent. Teenagers lack of life experience and labor training. Their psychological quality is also very poor. The limitation of exam oriented education can never be broken through. In order to solve these problems, the Ministry of education put forward the rectification measures of sports professional education. Let physical education become a compulsory course for children. Put students' physical and mental health first. Nowadays, the learning method of network teaching is more and more popular. Based on the Internet, the sharing of physical education curriculum teaching resources has become an innovative way for students to learn sports curriculum content. This paper puts forward the current situation of the sharing of physical education teaching resources. This paper also puts forward the design principle of shared resource platform. On this basis, this paper puts forward specific strategies for the construction of shared resources.